EFFECT OF DISPERSING AND STABILIZING ADDITIVES ON RHEOLOGICAL CHARACTERISTICS OF THE UPGRADED BROWN COAL WATER MIXTURE - DATIN F. UMAR; BUKIN DAULAY (Puslitbang tekMIRA, 2008)
The preparation of upgraded brown coal water mixture (UBCWM) by using an Indonesian upgraded coal that was produced by an upgraded brown coal (UBC) process in pilot scale, was carried out to obtain the effect of dispersing and stabilizing additives on rheological behaviour of the UBCWM. Three kinds of anionic dispersing additives, naphthalene sulfonate formaldehyde condensate (NSF), polymethacrylate (PMA) and polystyrene sulfonate (PSS) and three kinds of stabilizing additives, carboxyl methyl cellulose (CMC) an organic material a derivative of cellulose, rhansam gum (S-194) and gellan gum (S-60) some kinds of bio poly sacharide the trade mark of Dainippon Pharma- ceutical Co. Ltd. were used in this study. Results indicate that the addition of NSF 0.3 wt% together with S-194 0.01 wt% is effective in preparing UBCWM with good slurry ability and stability, based on its rheological characteristics (apparent viscosity at shear rate of 100 s-1 and yield stress at zero point of shear rate). Since the price of S-194 is expensive, the addition of CMC 0.01 wt% is also effective in preparing stable UBCWM.